Analisis Kinerja Pegawai Pada Komisi Pemilihan Umum (KPU) Kabupaten Pohuwato: Studi Evaluatif di Tengah Dinamika Konflik Sosial dan Sengketa Konstitusional Tahun 2024 - Aprilani Parengring; Hasman Umuri; Riskal Nusi (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
This study presents an in-depth and comprehensive analysis of the performance of employees within the Secretariat of the General Election Commission (KPU) of Pohuwato Regency, Gorontalo Province, in welcoming and implementing a series of stages of the General Election (Pemilu) and Regional Head Election (Pilkada) in 2024. This study dissects the dimensions of work quality, quantity, timeliness, and discipline of State Civil Apparatus (ASN) and supporting staff amidst two waves of major crises ("twin shocks"): security instability following the mass riots of September 2023 that paralyzed the regional government center, and legal-administrative pressure due to the Constitutional Court Decision mandating a Revote (PSU) for the Gorontalo Provincial DPRD Electoral District 6. The main findings indicate that the KPU of Pohuwato Regency demonstrated a high level of bureaucratic resilience, evidenced by the success of maintaining the continuity of the election stages without incidents of logistical failures, the success of defending administrative arguments in disputes over results at the Constitutional Court, and the safe execution of the PSU. However, the analysis also highlights the vulnerability of ad hoc human resource management to fatigue and the challenges of maintaining voter turnout amid post-conflict apathy.